Prevalence, socio-demographic determinants, and self-reported reasons for hysterectomy and choice of hospitalization in India - Priyanka Kumari; Jhumki Kundu (BMC, 2022)
Abstract Background There is limited evidence of hysterectomy in India because of a lack of data in large-scale, nationally representative health surveys. In 2015-16, the fourth National Family Health Survey (NFHS-4)-a cross-sectional survey-collected for the first-time direct information on hysterectomy and self-reported reasons for undergoing the procedure among women in the reproductive age group. The current study evaluates the prevalence, determinants, and choice of hospitalization (Public vs. Private) for conducting hysterectomy in India among women aged 15-49 years in 29 states and seven union territories (UTs) based on the new large-scale population-based nationally representative dataset (NFHS 5). Methods Cross-tabulations and percentage distributions were utilized to analyse the prevalence of hysterectomy and the choice of hospitalization (public vs. private) across different socioeconomic backgrounds and reasons for undergoing hysterectomy. A multivariate binary logistic regression model was also used to find statistically significant determinants of hysterectomy. Results In India as a whole, 3.3% of women aged 15-49 years had undergone a hysterectomy. The percentage of women who had undergone the procedure was found to vary considerably across the states and the UTs. The southern region stands out for the considerably higher prevalence of hysterectomy; particularly in the states of Andhra Pradesh (8.7%) and Telangana (8.2%), the prevalence was very high followed by Bihar (6%) and Gujrat (4%). On the other hand, the North-eastern region had the lowest prevalence of hysterectomy (1.2%). A noticeable fact that emerged was that the majority of the hysterectomies were performed in the private sector (69.6%) in India. But the scenario was quite different in north-eastern region as in this region more hysterectomies were performed in public health facilities (73%) rather than private health facilities (26.7%). Age, place of residence, religion, caste, level of education, geographic region, wealth quintiles, parity, age at first cohabitation of women were found to be the socio-demographic determinants statistically associated with hysterectomy in India. The likelihood of hysterectomy was higher among women living in rural areas (AOR: 1.3, CI: 1.23-1.35), in the richest wealth quintile (AOR 2.6; CI 2.37-2.76) and in the southern region (AOR 1.6; CI 1.47-1.66). The reasons frequently reported for hysterectomy were excessive menstrual bleeding/pain, followed by fibroids/cysts. Conclusion This study has attempted to analyse hysterectomy prevalence and its socio-economic determinants using the latest fifth round of NFHS data of all the states and covering 21 states and union territories of India, which gives wider coverage of hysterectomy and more recent with accurate data. More research is needed therefore to unravel the complex dynamics of hysterectomy in India (and elsewhere) which could be used to help women make more informed choices and in turn advance their reproductive health and rights.